2003
DOI: 10.1021/ol0351448
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 2-Polyfluoroalkylchromones with 1,3,3-Trimethyl-3,4-dihydroisoquinolines and Methylketimines as a Direct Route to Zwitterionic Axially Chiral 6,7-Dihydrobenzo[a]quinolizinium Derivatives and 2,6-Diaryl-4-polyfluoroalkylpyridines

Abstract: [reaction: see text] 2-Polyfluoroalkylchromones react with 1,3,3-trimethyl-3,4-dihydroisoquinolines to give zwitterionic axially chiral 6,7-dihydrobenzo[a]quinolizinium derivatives in high yields. In addition, performing this reaction with aromatic methylketimines is a simple and convenient synthesis of 2,6-diaryl-4-polyfluoroalkylpyridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…During the last decade Sosnovskikh [128,[194][195][196][197][198][199][200][201] and his group continued to devote great attention to the chemistry of 2-(polyhaloalkyl)chromones (2-R F -chromones) 185, particularly 2-(polyfluoromethyl)chromones (2-CF 3 -chromones) [52]. Some of their possible reactions are depicted in (Scheme 60): the reaction with ketimines leading to compounds 186-189 [194,196,198]; with acetophenones in the presence of lithium diisopropylamide to give 2-aroylmethyl-2-R F -chromanones 190 [197]; and a novel annulation reaction with salicylaldehydes in the presence of piperidine that constituted a direct route to chromeno [2,3-b]chromen-11-ones 191 by a tandem intermolecular oxa-Michael addition and subsequent intramolecular Mannich condensation [195].…”
Section: Reactivity Of Halomethylchromonesmentioning
confidence: 99%
“…During the last decade Sosnovskikh [128,[194][195][196][197][198][199][200][201] and his group continued to devote great attention to the chemistry of 2-(polyhaloalkyl)chromones (2-R F -chromones) 185, particularly 2-(polyfluoromethyl)chromones (2-CF 3 -chromones) [52]. Some of their possible reactions are depicted in (Scheme 60): the reaction with ketimines leading to compounds 186-189 [194,196,198]; with acetophenones in the presence of lithium diisopropylamide to give 2-aroylmethyl-2-R F -chromanones 190 [197]; and a novel annulation reaction with salicylaldehydes in the presence of piperidine that constituted a direct route to chromeno [2,3-b]chromen-11-ones 191 by a tandem intermolecular oxa-Michael addition and subsequent intramolecular Mannich condensation [195].…”
Section: Reactivity Of Halomethylchromonesmentioning
confidence: 99%
“…We demonstrated that chromones 1 react with dihydroisoquinolines and methyl ketimines to give 2,6-diaryl-4-trifluoromethylpyridines (preliminary communication, see Ref. 5 ). This result and the literature data 4k clearly showed that the present approach could be also applicable to chromones 1 and amidines (1,3-N,N-dinucleophiles), providing the corresponding 4-polyfluoroalkylpyrimidines.…”
mentioning
confidence: 99%
“…Recently, 5 in continuation of our studies on the chemical properties of 2-polyfluoroalkylchromones 1, which turned out to be highly reactive substrates in the reactions with N-, 6a,b S-, 6c,d and C-nucleophiles, 6e,f we investigated the reactions of these compounds with 1,3,3-trimethyl-3,4-dihydroisoquinolines and aromatic N-substituted methyl ketimines capable of reacting with electrophilic substrates as 1,3-C,N-dinucleophiles due to the enamine tautomeric form. We demonstrated that chromones 1 react with dihydroisoquinolines and methyl ketimines to give 2,6-diaryl-4-trifluoromethylpyridines (preliminary communication, see Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Calcd for C 18 H 13 ClF 3 NO 4 Á1.5H 2 O: C, 50.66; H,3.78; N, 3.28. Found: C, 50.45;H, 3.80; N, 3.19.…”
mentioning
confidence: 99%